Endogenous Pancreaatic Regeneration from Pancreatic Duct Epithelium in Diabetic Adult Rats - Jaumah, Zauhair A.; AL-Khafhaji, Fadhil A.; AL-Khalisi, Maan H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Deficiency in beta cell mass is the hallmark of most forms of diabetes, it is worthwhile understanding pancreatic regeneration in the context of this disease.Of crucial importance in the development of diabetes, both type I and type II, is the insufficient beta cell replication after the onset of disease.This is why we are always in search of new sources of beta cells to be generated by neogenesis to induce beta cells. In this regard, pancreatic stem or progenitor cells may offer a promising therapeutic approach for diabetes. Methods and Materials: A total of 60 adults swiss albino rats were divided into two groups. Group I, control group (30 animals) were injected with normal saline into the subcutaneous and pancreatic tissue, and group II (30 animals) were exposed to 90% subtotal pancreatectomy for the study of the possible regeneration, and trans-differentiation of pancreatic stem cells from pancreatic duct epithelium into functioning islet cells. Results: The animals of group II showed high blood glucose and normal serum AFP during the period of experiment. The histological study revealed regeneration and proliferation of small cells from epithelial cells of the pancreatic duct during the first three weeks of the experimental period and then formation of islet like cells attached to epithelium of pancreatic duct around the period of six weeks. The animals of group I (control group) showed no changes in the pancreas. Conclusion: Pancreatic islet cells may originate from pancreatic duct epithelium.